EFEKTIFITAS KONSUMSI SELANG DAUN KELOR DAN DAUN MIMBA UNTUK MENGONTROL KADAR GULA DARAH PADA PASIEN DIABETES DI DESA JARIN KECAMATAN PADEMAWU - Layla Imroatu Zulaikha; Yulia Paramita (Wiraraja Medika : Jurnal Kesehatan, 2017)
Diabetes mellitus is a disease characterized by high blood sugar levels caused by a disturbance in insulin secretion or insulin related disorders or even both herbal treatments can treat diabetes mellitus and keep the sugar levels normal by restoring the pancreas organ and improving the sensitivity of the cells body. If the pancreas has returned to health then it can automatically perform its function properly ie to produce enough insulin. This research is a research to examine the effect of treatment on the behavior that arise as a result of treatment. This research was conducted to determine the blood sugar levels after doing the consumption of the hose between the leaves of mimba leaves. The first semester focuses on the effectiveness of blood sugar decrease in diabetic patients with sugar content <300 gr / dl, with system of daily consumption of hose 3 times with composition of moringa leaf, mimba leaf and moringa leaf. The second semester focuses on the effectiveness of decreasing blood sugar level in diabetic patients with sugar content <300 gr / dl, with system of daily consumption of 3 times daily with composition of mimba leaves, moringa leaves and leaves. In addition, the study also obtained information on the effectiveness of Moringa leaf hose and mimba leaves to cope with the increase in blood sugar levels for diabetics.